Комбінативна внутрішньовидова гібридизація в селекції Beta vulgaris L. - Корнієнко, С.І.; Горова, Т.К. (Фактори експериментальної еволюції організмів, 2013)
Aims. To speed up the selection process twice for the biennial of culture a table beet peony Eclipse already offered an effective scheme for new-maturing genotypes, which is already based on the open pollination (polikrose) adaptive four derivatives sources round peony Bordo bekrosirovanie derived from F1 hybrid parent. Methods. Pollination of the hybrid, which has already received bekros F1 hybrid with the previous F1 has made it possible to get a generation that has ensured the standard uterine oval odnotipichnyh harvested roots to 98 % in variety Diy. Results. To speed up the selection of late-maturing varieties have a scheme that involves hybridization of derivative forms tapered and rounded. Conclusions. The selection on the selective background with F1 hybrid uterine betanin’s mather roots and propagation of in vitro culture has allowed for 12 years to reduce the creation of a new genotype varieties Bahriany.